Fucoidan–Fucoxanthin Ameliorated Cardiac Function via IRS1/GRB2/ SOS1, GSK3β/CREB Pathways and Metabolic Pathways in Senescent Mice - Chang, Po-Ming; Li, Kuan-Lun; Lin, Yen-Chang (Marine drugs, 2019)
The effects of low molecular weight fucoidan (LMWF) in combination with high-stability fucoxanthin (HSFUCO) on cardiac function and the metabolic pathways of aging mice (Mus musculus) were investigated. We demonstrated that LMWF and HSFUCO could improve cardiac function in aging mice. Aging mice were treated with LMWF and HSFUCO, either on their own or in combination, on 28 consecutive days. Electrocardiography and whole-cell patch-clamp were used to measure QT interval and action potential duration (APD) of the subjects. Cardiac tissue morphology, reactive oxygen species, and Western blot were also applied. Ultra-high-performance liquid chromatography–quadrupole time-of-flight (UPLC-QTOF) mass spectrometry was used for investigating metabolic alterations. The use of LMWF and HSFUCO resulted in improvements in both ventricular rhythms (QT and APD). Treatment with fucoidan and fucoxanthin reduced the expression levels of SOS1 and GRB2 while increasing GSK3β, CREB and IRS1 proteins expression in the aging process. Three main metabolic pathways, namely the TCA cycle, glycolysis, and steroid hormone biosynthesis, were highly enriched in the pathway enrichment analysis. When taken together, the LMWF and HSFUCO treatment improved both the ventricular rhythm and the muscular function of aging subjects by interfering with the metabolism and gene function.